Effect of dexamethasone with granisetron or ondansetron for prevention of post-operative nausea vomiting in patients undergoing laparoscopic gynaecological surgery - Sharma, Shailendra Kumar; Singh, Shalendra; Paul, Debashish; Ameta, Nihar; Taank, Priya; Singh, Tina (International Journal of Research in Medical Sciences, 2020)
Background: Post-operative nausea and vomiting (PONV) is generally self-limiting, associated with high level of patient dissatisfaction and may delay hospital discharge. The anaesthetist is usually blamed, despite evidence that PONV results from a variety of factors and variety of antiemetic drug available in market. With this issue we aim to compare the effectiveness of dexamethasone with granisetron or ondansetron in patients undergoing laparoscopic gynaecological surgery. Methods: 120 patients were registered in this prospective, randomized double blind study. Group I (n=60) received ondansetron 4 mg intravenously (IV)+dexamethasone 8mg I/V or II (n=60) received granisetron 1 mg IV+dexamethasone 8 mg I/V prior to anaesthesia. Post-operative data of PONV was recorded at pre-defined intervals. Results: The majority of the patients were of the age group 20-25 years (55.83%). The mean score of Group I subjects was 0.30±0.72 and that of Group II was 0.20±0.57 (p=0.43). There are 3.33% of patients in group-I having vomiting episodes, and 1.67% of patients in group-II having vomiting episodes, none of the patients developed 2nd episodes of vomiting in either group. Thus it appears that dexamethasone in combination with ondansetron and granisetron is effective in decreasing the number of episodes of PONV. The occurrence of sickness episodes within 24 hours of surgery revealed no significant different in both groups. Haemodynamic variables showed no significant difference recorded in postoperative care unit between the study groups. The most common complaint was headache 16.67% in both groups. Conclusions: Dexamethasone 8 mg with either granisetron 1 mg or ondansetron 4 mg showed no significant difference in antiemetic efficacy with minimal side effects and excellent patient satisfaction.